2016
DOI: 10.5751/es-08482-210325
|View full text |Cite
|
Sign up to set email alerts
|

Global environmental change: local perceptions, understandings, and explanations

Abstract: Global environmental change (GEC) is an increasingly discussed phenomenon in the scientific literature as evidence of its presence and impacts continues to grow. Yet, while the documentation of GEC is becoming more readily available, local perceptions of GEC— particularly in small-scale societies—and preferences about how to deal with it, are still largely overlooked. Local knowledge and perceptions of GEC are important in that agents make decisions (including on natural resource management) based on individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 121 publications
1
78
0
2
Order By: Relevance
“…Although most responses to global environmental change are focused on the diversification of production strategies (Pyhälä et al. ), in the Samiria basin, the Cocama people have intensified fishing. In this case, people's adaptations are reflecting the shifts in animal populations, which ultimately helps maintain food and income benefits and sustainable use.…”
Section: Discussionmentioning
confidence: 99%
“…Although most responses to global environmental change are focused on the diversification of production strategies (Pyhälä et al. ), in the Samiria basin, the Cocama people have intensified fishing. In this case, people's adaptations are reflecting the shifts in animal populations, which ultimately helps maintain food and income benefits and sustainable use.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may be due to inadequate cover of this area by meteorological stations. Furthermore, misperception could derive from misunderstanding of causes and effects (Hitayezu.et al 2017) and from attributing to climate change the severity of impacts influenced even by other factors, such as increased population and inadequate land management practices (Pyhälä et al 2016). In the Jimma study area, participants in our study reported higher stability of climate conditions over the last decades.…”
Section: Stakeholders' Perceptions On Climate Changementioning
confidence: 99%
“…Small-scale societies, including those found in drylands, are often located in rural contexts with frequent exposure to, and high dependency on, local food-production processes and related activities. As a result, members of smallscale societies have often developed robust social-ecological bonds and have a more marked temporal, spatial, and social proximity with issues related to climate change (IPCC 2012), which define the perception of and response to external stressors (Pyhälä et al 2016). Specifically, being consistently exposed to climate variability and extremes, small-scale societies in drylands have maintained a strong sense of environmental awareness that enables them to make an informed evaluation of the potential effects of local temperature rise, related hazards, and possible responses, e.g., concerning food production systems (Wildcat 2013).…”
Section: Pillars Of Resilience In Small-scale Societiesmentioning
confidence: 99%